Digital class D amplifier with negative feedback - Sun, Song. (2009)
Class D audio power amplifiers have become more prevalent in consumer electronics products because of their high power efficiency and low power dissipation. However, some of the drawbacks of Class D amplifiers include circuit complexity, high Total Harmonic Distortion (THD), high switching noise etc. A Class D amplifier typically consists of three blocks: a modulation circuit, a digital output stage and a low pass filter.